Politicas públicas, orçamento público e judicialização da saúde: o papel do Ministério Público na garantia do acesso à saúde em tempos de pandemia - Bernardes, Fáustone Bandeira Moraes (Universidade Federal do Tocantins, 2024)
The vocation of the Public Ministry is to act in favor of the effectiveness of the right to health, since the actions and services aimed at guaranteeing it have public relevance (Article 197 of the Brazilian Constitution) and are in the interest of the community, being unavailable. Based on this assumption, a main question is established as the generating problem of this dissertation: in the outlined time frame, did the MP satisfactorily use the legal instruments to guarantee access to health, more specifically, access to hospital beds and loss of vaccines? The hypothesis is that the MP-TO has important legal instruments to satisfactorily use the legal instruments to guarantee access to health, more specifically, access to hospital beds and loss of vaccines. The general objective of this dissertation is to evaluate the actions of the Public Ministry of Tocantins with problems generated by the pandemic, such as the supply of beds and loss of vaccines. As specific objectives, it is expected: to address aspects related to public policy, public budget and Public Ministry, where the concept of public policy and the ways of measuring its effectiveness are described, as well as to describe the role of the public budget as a means of implementing public policies and discussing the Public Prosecutor's Office and Public Policies; describe the constitutional weaknesses in facing public policies in the health area in times of the covid-19 pandemic, highlighting the problem of the constitutional powers of federal entities and mentioning the jurisprudence on the constitutional crisis and data on the pandemic in Brazil and how the covid-19 pandemic was faced in the State of Tocantins and in its municipalities and describe the MP-TO, its organization and the Public Policies in the area of health and evaluate the performance of the MP-TO to guarantee the Public Health Policies in the Pandemic from covid-19. This is a descriptive and exploratory study with a qualitative approach. This approach was chosen due to the difficulty of finding all numerical data on the subject addressed in this dissertation. The universe of the research are MP-TO actions regarding vaccine losses. The unit of analysis will be the CAUSAÚDE (Health Operational Support Center) and the actions proposed by the MP-TO in the period 2021 and 2022 will be analyzed. It was possible to verify that the Public Prosecutor's Office of Tocantins acted continuously in the face of covid-19, however, some questions cannot be answered, especially those related to the decrease in deaths by covid-19 due to the actions of the Public Prosecutor's Office of Tocantins . In any case, it was possible to verify the actions of the Public Ministry of Tocantins to face the covid-19 pandemic, demonstrating that, as far as possible, it used the legal instruments it had to guarantee access to health, more specifically, access to hospital beds and losses of vaccines.